Penerapan Model Pembelajaran Contextual Teaching And Learning (CTL) Dalam Membentuk Karakter Siswa Pada Mata Pelajaaran Agama Hindu Dan Budi Pekerti Di SD Dwijendra Denpasar Tahun Pelajaran 2021/2022 - Putu Rusmita Sari; Heny Perbowosari Perbowosari; I Putu Andre Suhardiana (UHN IGB Sugriwa Denpasar, 2023)
The formation of student character is the main thing that must be done. Especially in the midst of rampant morality problems due to a character crisis among the younger generation. Therefore, it is important to internalize character values in the learning process, especially in the implementation of Hindu religious subjects and character. Assertive strategy so that the integration of character values in learning activities becomes more interesting can be done by applying the Contextual Teaching and Learning (CTL) learning model. The purpose of this study is to describe the application of the Contextual Teaching and Learning (CTL) learning model in shaping students' character, describe the obstacles and identify the efforts made to overcome the obstacles and to analyze the implications of the application of the Contextual Teaching and Learning (CTL) learning model in shaping students' character. In this research, the researcher uses constructivism theory, behaviorism theory and character theory. This type of research is descriptive qualitative. The results of this study are as follows: 1) The application of the CTL learning model is carried out in three stages, namely the planning stage, the implementation stage and the evaluation stage, in these three stages the teacher implements the components of the CTL learning model including constructivism, inquiry, questioning, modeling, reflection and assessment authentic. 2) Constraints faced include student study habits, student discipline and lack of time to make learning media. 3) Efforts made to overcome obstacles are by giving warnings, giving punishments and prioritizing time to make learning media. 4) The implications of applying the CTL learning model in shaping students character are increasing students religious attitudes, increasing students independence, forming students awareness to work together and increasing students awareness to be honest.